• It is something you can obtain by substituting (-5) for x in the "g" equation, then substituting that answer for x in the "f" equation.
  • First you've got to find g(-5) i.e.....put -5 in the place of 'x' in g(x)=(x-3)/2......... Therefore...g(-5)=-5-3/2 =-8/2 g(-5)=-4. Now you know what g(x) den comes f[g(-5)]i.e. f(-4)....put -4 in the place of 'x' in f(x)=2x+3 =2(-4)+3 =-8+3 =-5. Here comes your answer...f[g(-5)]=-5...

Copyright 2023, Wired Ivy, LLC

Answerbag | Terms of Service | Privacy Policy